2022
DOI: 10.3389/fmicb.2022.844968
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and Metabolomic Insights Into the Mechanism Underlying the Disparity in Milk Yield of Holstein Cows

Abstract: This study was conducted to investigate the metabolic mechanism underlying the disparity in the milk yield of Holstein cows. Eighteen lactating Holstein cows in their second parity and 56 (±14.81 SD) days in milking (DIM) were selected from 94 cows. Based on the milk yield of the cows, they were divided into two groups of nine cows each, the high milk yield group (HP) (44.57 ± 2.11 kg/day) and the low milk yield group (LP) (26.71 ± 0.70 kg/day). The experimental cows were fed the same diet and kept under the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…A study focusing on the rumen microbial genomes observed that the Refseq database classified only about 50% of reads [ 33 ]. However, it is worth noting that the average milk yield for the low-producing group in our study was still greater than the average milk yield (44.57 kg/d) reported by others for their high-producing group [ 12 ]. Additionally, the two groups considered in the study had a difference of milk production of almost 20 kg/d [ 12 ], for the current study the groups only had a difference in milk production of about 10 kg/d when comparing the high versus low production by GPTAM.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…A study focusing on the rumen microbial genomes observed that the Refseq database classified only about 50% of reads [ 33 ]. However, it is worth noting that the average milk yield for the low-producing group in our study was still greater than the average milk yield (44.57 kg/d) reported by others for their high-producing group [ 12 ]. Additionally, the two groups considered in the study had a difference of milk production of almost 20 kg/d [ 12 ], for the current study the groups only had a difference in milk production of about 10 kg/d when comparing the high versus low production by GPTAM.…”
Section: Discussioncontrasting
confidence: 80%
“…However, it is worth noting that the average milk yield for the low-producing group in our study was still greater than the average milk yield (44.57 kg/d) reported by others for their high-producing group [ 12 ]. Additionally, the two groups considered in the study had a difference of milk production of almost 20 kg/d [ 12 ], for the current study the groups only had a difference in milk production of about 10 kg/d when comparing the high versus low production by GPTAM. Differences in microbial relative abundances of some bacteria such as Proteobacteria were observed in another study comparing rumen microbial communities and metabolites of high versus low producing cows [ 10 ].…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations